Influence of Glomus species I: growth, N2 fixation, nodulation and root colonization of peanut - Hashim, Azizah; Khan, Mohd Imran; Mustaffa, Rizainal (Penerbit Universiti Kebangsaan Malaysia, 1997)
Peanut (Acrachis hypogea L.) var. Matjam grown in an Ultisol obtained from peanut field, was respectively inoculated with Glomus mosseae and G. velum. Responses of the host plant to treatments was estimated by periodic measurements from the fourth to twelfth weeks, for dry shoot and root weight, nodulation, N2 fixation (C2H2 reduction activity), per cent root colonization and vesicle formation cm-1 root. A proportionate increase in dry weight of root and shoot was observed with increase in sampling time up to the eight and tenth weeks, respectively. This increase was only significant only in the 10th week for shoot and 8th week for dry weights when compared to that of uninoculated control plants (indigenous species only present). However, the difference between the two Glomus species was not a significant for all the samplings. The nodule number plant-1 and N2 fixation was maximum and significant in the 8th week when compared to uninoculated controls. However, there was a sharp decline in nodulation and N2 fixation in both the treated and uninoculated plants after this week. This decrease was significant (P < 0.05) in G. mosseae treatment (at the 12th week for nodulation and 10th - 12th week for N2 fixation). The difference between G. mosseae and G. velum was not significant (except, in the 8th and 12th week) for N2 fixation. Percentage root colonization and formation of vesicle cm-1 root system was significantly higher in G. mosseae and G. velum plants compared to controls. However, the formation of vesicle was not significantly different at 12th week of observation. Plant responded positively to G. mosseae by forming more vesicle than in G. velum or indigenously colonized plants.